Biomedical engineering applications: cell engineering - Abdul Hamil, Muhammad Mahadi (Penerbit UTHM, 2017)
This book comprises of four chapters demonstrating the studies which involve cell culture with bioinstrumentation experimental work identifying the potential solutions for wound healing applications via exploitation of high voltage electric field or micro second pulse. The high voltage exposure on cells have shown interesting findings which gives us an idea on how to develop a dug free wound healing method in the nearest future. The book also consists of two chapters that will present about the investigation of bone microstructures acquired from human samples. In this study there will be combination of bone histomorphology, imaging processing and computational method analysis thus also a new biomedical engineering application. Traditionally, the investigation of bone microstructures was performed by forensic officer by looking through microscope and their expert estimation by years of experience. However, by having the engineers joining this investigation we could help the forensic officer to perform the analysis through computational method and automated analysis. Therefore the accomplishment of the six chapters will give an idea for the reader on what to expert in the field of research the so called “Cell Engineering”.